ANALISIS HERMENEUTIKA TERHADAP NUBUATAN YESUS DALAM INJIL MATIUS 16:28 - Malik, Malik (Sekolah Tinggi Teologi Injili Indonesia Bali, 2024)
The Gospel of Matthew 16:28 is one of the verses considered difficult for early readers, even some theologians. This is evident from the emergence of various interpretations related to the verse. The part considered difficult is Jesus' statement about some of His disciples who will not die before seeing Jesus come in His Glory. The problem that is considered difficult to answer is whether it is possible for anyone to see Jesus coming in His glory as king in His kingdom? Where from the many Bible statements the coming of Jesus as king will only occur at His second coming at the end of time. Who is the disciple referred to by the Lord Jesus, who can see His coming?The method used in this research is Hermeneutic analysis with a text, context, and historical approach. The text of the Gospel of Matthew 16:28 will be analyzed, then the writer will analyze the relationship between the previous verses or passages, especially chapters 16:13-27. Next, the writer will analyze it with the following text, namely chapter 17:1-9. The author will also analyze other texts that are directly or indirectly related. The texts in question are 2 Peter 1:16-21, Matthew 24-25, texts related to the suffering of people who are believed, and the last is the context of the book of Revelation. The results of the analysis show that some of the disciples saw the coming of Jesus in glory as the son of the Father in His kingdom.